2020
DOI: 10.1111/bjd.19025
|View full text |Cite
|
Sign up to set email alerts
|

Is psoriasis associated with dementia or cognitive impairment? A Critically Appraised Topic*

Abstract: Clinical question Is psoriasis associated with dementia or cognitive impairment? Background Psoriasis is a multisystemic inflammatory disorder that has an unclear association with cognitive dysfunction. Objectives To conduct a Critically Appraised Topic that synthesizes the results from relevant observational studies. Methods A systematic literature search of PubMed and Embase was conducted on 12 July 2019 to identify case-control, cross-sectional or cohort studies that investigated the association between pso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
0
25
0
2
Order By: Relevance
“…Guilt and self-blame have been reported among the emotions experienced by parents of children with atopic dermatitis (AD). 3 In this cross-sectional study, which included 1063 parents of children with AD between 6 and 17 years old selected from a representative sample of the French population, we observed that 251 parents (23.6%) reported that they felt guilty for their child's AD. The fact that the recruitment did not take place in a hospital or in dermatological practice may allow to detect parents of patients who were diagnosed with AD, but who do not go regularly to the hospital or to the dermatologist, since, for example, they have a mild condition.…”
Section: Feelings Of Guilt In Parents Of Children With Atopic Dermatitismentioning
confidence: 84%
See 1 more Smart Citation
“…Guilt and self-blame have been reported among the emotions experienced by parents of children with atopic dermatitis (AD). 3 In this cross-sectional study, which included 1063 parents of children with AD between 6 and 17 years old selected from a representative sample of the French population, we observed that 251 parents (23.6%) reported that they felt guilty for their child's AD. The fact that the recruitment did not take place in a hospital or in dermatological practice may allow to detect parents of patients who were diagnosed with AD, but who do not go regularly to the hospital or to the dermatologist, since, for example, they have a mild condition.…”
Section: Feelings Of Guilt In Parents Of Children With Atopic Dermatitismentioning
confidence: 84%
“…For example, in patients with psoriasis, 5 it was studied as a component of feelings of stigmatisation. To our knowledge, with the exception of the qualitative study by Chamlin et al, 3 the presence of feelings of guilt in parents of patients with AD has not been investigated. Our observation that such feelings are present in about a quarter of parents of children with AD shows that this aspect cannot be neglected.…”
Section: Feelings Of Guilt In Parents Of Children With Atopic Dermatitismentioning
confidence: 94%
“…Psoriasis has been found to be associated with an increased risk of cognitive impairment and dementia in most studies 30 . Marek‐Jozefowicz et al performed a cross‐sectional study to evaluate cognitive function in 97 severe psoriasis cases and 91 controls.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic review and meta-analyses summarized the association between dementia and psoriatic disease (Table 3) (92,93), however two population-based studies in Taiwan found contradictory results on the association between psoriasis and dementia (100,101). Phototherapy and systemic treatment might not have a protective effect against dementia in psoriatic patients (100).…”
Section: Dementiamentioning
confidence: 99%